The self and self-directed behaviors: A literature review of Brazilian case reports in Child Analytic-Behavior Therapy in the operant literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
The concept of self is related to the private control of the individual. When he fails to do this serious problems can occur such as personality disorders. This paper analyzes the use of the concept of self in the practice of Child Analytic - Behavioral Therapy (CABT). A literature review of all the volumes of three Brazilian scientific magazines and a collection of books on behavior analysis, selecting CABT publications addressing this topic or some self-directed behavior (N = 16) was performed. It was observed that some therapists have proposed to intervene only in partial aspects of self development, which entail to deficits on the objectives proposed by the Child Analytic - Behavioral Therapy. This result points to the relevance of the publication of new works that focus on the interventions on the self in CABT
Keywords: self; child behavioral therapy; case report